Efeito de uma intervenção focada em estratégias de regulação emocional de crianças sobre aspectos do comportamento, habilidades sociais e competência acadêmica no contexto escolar - Nathalia Santos da Costa (2014)
Emotional Regulation (ER) is important for social interaction and interferes in several contexts. In the educational field it can be related to the interactions quality and to school achievement. This research evaluated the ER interventions effect on students from the second grade of elementary school and the eventual impacts on behavioral, social abilities and school achievement indicators. Fifty six students and its 1st and 2nd year teachers from two municipal schools in Belo Horizonte took part in this research. Socioeconomic data and evaluation of general intelligence (Raven) demonstrated equivalence between the intervention group (IG) and control group (CG). The two groups were subjected to pre-intervention assessment through instruments: a) administered to children: Academic Performance Test (SPT), Assessment of Social Skills (SSRS-BR) and System Boards and Interview for Review of Emotional Regulation (EPRE) b) answered by teachers: SSRS-BR, Strengths and Difficulties Questionnaire (SDQ) and MTA-SNAP-IV for symptoms of inattention, hyperactivity / impulsivity. The students from IG attended 9 weekly meetings of 60 minutes each to stimulate emotions identification and regulation. After two months the two groups were reassessed. Results showed, in the evaluation of teachers: a) significant improvement, compared to all subscales of social skills and prosocial behavior in IG, b) significant worsening of problematic behaviors and self-control in CG c) reducing symptoms of hyperactivity / impulsivity and inattention in IG. The EPRE evaluation observed: a) increase in the correct identification of the representation of fear in IG; b) increase of experience, perception and use of strategies in case of happy; c) absence of significant differences in academic performance and self-evaluation of HS in both groups. The results suggest effects of the intervention focused on RE in the assessment of social skills by teachers in symptoms of inattention and hyperactivity, and as a protective factor in the development of behavioral problems, with no effect on school performance.